Application of Freeze-Dryers of Chamber Type in the Collections of Pathogenic Microorganisms - N. S. Chervyakova; T. V. Valova; A. V. Osin (Проблемы особо опасных инфекций, 2014)
By the example of Martin Christ Epsilon 2-6D device carried out was assessment of the possibility to use freeze-dryers of the chamber type for conservation of pathogenic microorganisms collection strains. Elaborated was algorithm of lyophilisation of the III-IV pathogenicity groups bacteria, which incorporated conditions of freeze-drying and biological safety provision of this process. Indices of viability and survivability were defined for freeze-dried cells of pathogenic bacteria strains. Using thermostability test calculated were predicted timelines of storage of collection strains preparations freeze-dried in the flasks in Martin Christ Epsilon 2-6D. It was determined that in the collections of pathogenic microorganisms freeze-dryers of the chamber type could be used most prospectively for the III-IV pathogenicity groups bacteria conservation requiring mass reproduction and not intended for long storage. At the same time their application for freeze-drying of the strains of the I-II pathogenicity groups bacteria intended for a long storage, requires further adaptation of these devices as regards biological safety provision and prolongation of the shelf life.